Workflow patterns as web service compositions: the case of PEWS - Guerra, Marcelo (2012)
In the past years, Web Services (WS) have become the standard for exposing services as application programming interfaces to be consumed from anywhere in the world. Since many operations require the collaboration between two or more WS, the need to have languages to express Web Service Compositions has emerged. Web Service Composition presents a problem very similar to Business Process Management (BPM), both disciplines aim to express complex combinations of operations to achieve broader goals. In BPM these combinations are generally known as Workflows. The current industry standard for representing Web Service Workflows is BPEL, a language developed by Microsoft, IBM and others. PEWS is another language proposed to describe Web Service Compositions. Simplicity and neatness of descriptions are two relevant features of this language. This work proposes some extensions to PEWS in order to support the most common workflow patterns. The extended version of PEWS is able to fully support 36 out of the 43 Workflow Control Patterns as defined in the literature. This new version creates the foundation for further studies on the language, especially future extensions to capture other patterns and features (such as data manipulation, error handling, etc.) as well as the addition of semantic information to compositions.